The impact of selective episiotomy on maternal short-term morbidity: a retrospective study - Gazal Radner; Lukas Jennewein; Dörthe Brüggmann; Frank Louwen; Ammar Al Naimi (Taylor & Francis Group, 2024)
Background The aim is to investigate the risk of short-term maternal morbidity caused by the selective clinical use of episiotomy (rate < 0.02), and to compare the risk of severe perineal tears with the statewide risk.Methods In this retrospective cohort study, we investigated the effect of selective episiotomy on the risk of severe perineal tears and blood loss in singleton term deliveries, using propensity scores with inverse probability weighting.Results This study included 10992 women who delivered vaginally between 2008-2018. Episiotomy was performed in 171 patients (1.55%), three of whom (1.75%) experienced severe perineal tears compared to 156 (1.44%) in the control cohort. The adjusted odds ratio of severe perineal tears was 2.06 (95% confidence interval [CI]: 0.51, 8.19 with 0.3 p value). Multivariate linear regression showed that episiotomy increased blood loss by 96.3 ml (95% CI: 6.4, 186.2 with 0.03 p value). Episiotomy was performed in 23% (95% CI: 0.228, 0.23) of vaginal deliveries in the state of Hessen, with a risk of severe perineal tears of 0.0143 (95% CI: 0.0139, 0.0147) compared to 0.0145 (95% CI: 0.0123, 0.0168) in our entire cohort.Conclusions Selective use of episiotomy does not increase the risk of higher-grade perineal tears. However, it may be associated with maternal morbidity in terms of increased blood loss.